α,β-Glucan Complex in Saccharomyces carlsbergenesis - P. JADHAV, JYOTI; S. DAKE, MANJUSHA; B. PATIL, NARAYAN (Asian Journal of Chemistry, 2010)
The two pools of glycogen present in Saccharomyces carlsbergenesis one is the soluble pool and intracellular, the remainder water insoluble linked with cell wall β-glucan. Glycogen is universally assigned the role of an energy reservoir and is always present intracellularly. The intracellular pool of glycogen which could be broken down to yield glucose and further used for production of energy required for metabolic activities. The soluble pool of glycogen present in the Saccharomyces carlsbergenesis could have performed this function efficiently; however the presence of an alternate pool in the cell wall would indicate that its physiological role should be different from that of the soluble glycogen. It is demonstrated that this glycogen can be synthesized using the alkali insoluble cell wall pellet as a primer. The attachment of cell wall glycogen to β-glucan was established in laboratory through the use of (1→3)-β-D-glucanase, β-glucosidase and lyticase enzymes, used for solubilization of cell wall linked glycogen, concanavalin A sepharose CL-4B affinity chromatography and molecular sieving has confirmed that glycogen is linked to β-glucan. Further partial acid hydrolysis and subsequent paper chromatography of the α,β-glucan complex revealed the presence of gentiobiose and other higher oligosaccharide. This proved that glycogen is linked to β(1→3) through β(1→6) branch in Saccharomyces carlsbergenesis.